HISTORY OF THE DEVELOPMENT OF THE TRANSPORTATION SYSTEM OF UZBEKISTAN (1945-1990) - Saidusmanov Bakhrom Abduganiyevich (Bright Mind Publishing, 2026)
Today, the transport system occupies a special place in the world market. It is natural that service is an important factor of economic stability. From the first days of the establishment of Soviet power, the most important task was to manage the economy and end private ownership.
Keywords: National economy, Road transport, Roads, Convoys, cargo convoys, industrial enterprises, communication points, passenger and freight traffic volumes, new road operators.